2007
DOI: 10.1111/j.1463-6409.2007.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomy of endangered South and South‐east Asian freshwater turtles elucidated by mtDNA sequence variation (Testudines: Geoemydidae: Batagur, Callagur, Hardella, Kachuga, Pangshura)

Abstract: Phylogeny and taxonomy of endangered South and South-east Asian freshwater turtles elucidated by mtDNA sequence variation (Testudines: Geoemydidae: Batagur, Callagur, Hardella, Kachuga, 36 ,[429][430][431][432][433][434][435][436][437][438][439][440][441][442] Using DNA sequences of the mitochondrial cytochrome b gene, we investigated phylogeny and taxonomy of South and South-east Asian turtles of all species and subspecies of the genera Batagur, Callagur, Hardella, Kachuga and Pangshura. We found three major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 22 publications
6
81
0
Order By: Relevance
“…However, Praschag et al (2007) found no evidence for genetic distinctiveness of H. t. indi and synonymized it under a monotypic H. thurjii.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoisesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, Praschag et al (2007) found no evidence for genetic distinctiveness of H. t. indi and synonymized it under a monotypic H. thurjii.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoisesmentioning
confidence: 93%
“…Genetics of the species has been analyzed by Praschag et al (2007) who found no evidence of genetic distinctiveness between the two previously recognized subspecies (H. t. thurjii and H. t. indi) and therefore synonymized them. The karyotype is unknown.…”
Section: 3mentioning
confidence: 99%
“…Additionally, Praschag et al (2007) demonstrated that the formerly widespread species, Batagur baska (sensu lato), comprised at least two genetically distinct species. In a follow-up paper, Praschag et al (2008b) argued that based on priority, the more northern species (India to Myanmar) should retain the name B. baska and that the specific epithet affinis (Cantor 1847) was available for the southern spe- • Chelonian Research Monographs,No.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoises • Cmentioning
confidence: 99%
“…Various authors have debated the relationships among these genera (e.g., Loveridge and Williams 1957;McDowell 1964;Hirayama 1984;Gaffney and Meylan 1988;Capler and Moll 1990;Spinks et al 2004). Praschag et al (2007), using DNA sequences of the mitochondrial cytochrome b gene, examined the relationships of species then constituting the genera Batagur, Callagur, Kachuga, Pangshura, and Hardella. A key finding was that Description.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoises • Cmentioning
confidence: 99%
“…Praschag et al (2007), using mitochondrial DNA, investigated the genetic relationships of the genera Kachuga and Pangshura, including P. sylhetensis, and confirmed the monophyly of Pangshura. They found that P. smithii and P. tentoria were sister species, with P. tecta and P. sylhetensis their successive sister taxa.…”
Section: Conservation Biology Of Freshwater Turtles and Tortoises • Cmentioning
confidence: 99%